Spectral Design Method to Simulate Tunable Spectra of Various Light Sources Based on Multi-Channel LEDs - Zijian Tao; Xiaojie Zhao; Shanshan Li; Qi Dai (IEEE Photonics Journal, 2024)
Using a single light source to simulate tunable spectra of various light sources, such as International Commission on Illumination (CIE) standard illuminants, has attracted great interest. This can be realized through the spectral mixing of multi-channel LEDs. However, there is currently a lack of a general and comprehensive spectral-mixing method that can effectively achieve the target spectra with a minimized number of LED channels. In this work, we propose such a method. It begins by determining the desired wavelength range according to an eye-sensitivity threshold based on the V(λ) function. Subsequently, a strategy for LED component selection is introduced. Lastly, detailed spectral mixing strategies are presented: (i) when using a large number of LED channels, spectral mixing optimization for direct spectral-shape matching ensures favorable outcomes; while (ii) with a limited number of LED channels, solely relying on the effort of matching the spectral shape may lead to a significant deviation in correlated color temperature (CCT). To solve this problem, an additional step of color mixing is applied. Our proposed method demonstrates significant improvements over prior methods in terms of spectral and CCT matching quality, as well as using a reduced number of LED channels.